Videoendoscopic assessment of uncommon sites of upper airway obstruction during sleep - Maurer, Joachim T.; Stuck, Boris; Hein, Gerhard; Hörmann, Karl (Sleep and breathing, 2000)
Patients with sleep-disordered breathing (SDB) suffer from repetitive upper airway occlusion. Various techniques have been described to assess the site of upper airway collapse. In most cases the soft palate or the base of tongue, or both, are the major levels of obstruction; rarely, the larynx, including the epiglottis, are found to be involved. We present five cases in which sleep videoendoscopy finally revealed the true mechanism of the inspiratory airway behavior. Two patients were sent to our service because of inefficacy of nasal ventilation therapy. One had a floppy epiglottis that was being sucked into the glottis. The other had a normal larynx during videoendoscopy. Instead, common pharyngeal collapse could be detected. Increasing the pressure normalized sleep, breathing, and videoendoscopy. The third patient showed apneas due to the adduction of the lateral parts of his omega-shaped epiglottis. In another case, inspiratory fluttering of the vocal cords caused snoring and arousals. The last case came in for bilateral vocal cord palsy with heavy nocturnal desaturations suggesting airway closure. Yet, the pharynx and larynx remained open throughout the night. Sleep videoendoscopy is a convenient method to define the level and mechanism of occlusion in obstructive SDB, particularly if the larynx is involved. It is useful to rule out airway compromise in case of recurrent nocturnal hypoxemias. Thus the results of sleep videoendoscopy have a strong therapeutical impact.
Gesehen am 18.05.2022